Pengaruh Pendidikan Karakter Terhadap Pengembangan Diri pada Siswa di SMPN 1 Sumbawa Besar - Febrian Nur Al Fajri; Roni Hartono; Lukmanul Hakim (Fakultas Psikologi dan Humaniora- Universitas Teknologi Sumbawa, 2020)
Character Education in which there is an element of self-development is a conscious effort to improve the quality of the individual's self against the potential possessed through the experience and new knowledge gained by individuals during their life. The purpose of this study was to determine the effect of character education on self-development of students at SMPN 1 Sumbawa Besar. This research used descriptive quantitative approach. Meanwhile, data collection technique employed the Slovin formula. The number of sample participated in this study was 88 students coming from grade 7, 8, and 9. The research data were obtained using a research instrument in the form of two scales, namely the scale of character education and the scale of self-development. The results of the study portray that character education has an effect on self-development of students with a value of p = 0,000 / p <0.05 and R Square of 0.297 which means that the better the character education is applied, the higher the self-development of students is. Character education has an effect of 29.7% and 71.3% is influenced by other variables outside the study. Character education is in the good category with the highest aspect being the religious aspect, while self-development is in the good category with the highest aspect being the aspect of moral potential